Bolnišnične knjižnice in storitve za paciente - Praznik Bračič, Doroteja (Organizacija znanja, 2025)
Hospital libraries are essential for providing professional information and help with professional work and research to healthcare staff and for supporting patients. Following IFLA recommendations and other standards, they are expected to offer access to information as well as activities that relax, entertain and aid the healing process. Reading during hospitalization can reduce stress, anxiety and depression, while promoting recovery. At the University Rehabilitation Institute of the Republic of Slovenia Soča (URI Soča), the professional library also addresses patients’ needs through a specially adapted collection. This article presents the development of the Patient Library project and other library services for patients with disabilities. The project was designed to encourage reading in the hospital environment. The renovation of the collection took place during the COVID-19 pandemic. The existing materials were reviewed, expanded, professionally processed and placed in a dedicated space. Special attention was given to user groups unable to use traditional (printed) books; alternative reading formats were provided for them. Through these activities, the professional library at URI Soča complements the institution's therapeutic activities and contributes to improving patients’ psychological well-being. Future plans include developing a similar project for younger patients in the children’s department, along with additional initiatives to promote reading and reading culture in the hospital setting.
Keywords: biblioterapija; bibliotherapy; bolnišnice; disabled persons; hospitals; knjižnice za paciente; knjižnične storitve; knjižnične zbirke; libraries for patients; library collections; library services; osebe z oviranostmi; spodbujanje branja